Effectiveness of Digital Bication Application as a Preventive Intervention for Negative Body Image Behavior - Ayu Endang Purwati; Sri Wulan Ratna Dewi; Sri Utami Asmarani (LPPM STIKes Muhammadiyah Ciamis, 2026)
Background: Body dissatisfaction and negative perceptions of body image are common problems among adolescents, particularly adolescent girls, which can have adverse effects on mental health. The development of digital technology provides opportunities to deliver more flexible and accessible preventive interventions. Objective: This study aims to examine the effectiveness of the Bication digital application as a preventive intervention in reducing negative body image behavior among adolescent girls. Methods: This research employed a quantitative approach with a pre-experimental one-group pretest-posttest design. The sample consisted of 60 adolescent girls from the D3 Midwifery Study Program at STIKes Muhammadiyah Ciamis, semesters 2-4, who used the Bication application. The instrument used was the validated Multidimensional Body-Self Relations Questionnaire–Appearance Scale. Data analysis was conducted using the paired sample t-test to determine differences before and after the intervention. Results: The results showed a significant increase in positive perceptions of body image after using the Bication application (p < 0.05). Participants also demonstrated an overall decrease in negative body image behavior scores. Conclusion: The Bication digital application proved effective as a preventive intervention for reducing negative body image behavior among adolescent girls. Further development is recommended by expanding the scope of educational features and involving larger and more diverse samples.